Wrong Site Spine Surgery in the Veterans Administration. Issue 10 (December 2019) - Watts, Bradley V.; Rachlin, Jacob R.; Gunnar, William; Mills, Peter D.; Neily, Julia; Soncrant, Christina; Paull, Douglas E.
Abstract : Study Design: Basic descriptive analysis was performed for the incident characteristics of wrong level spinal surgery in the Veterans Health Administration (VHA). Objective: To determine the frequency of reported occurrence of incorrect spine level surgery in the VHA, causal factors for the events, and propose solutions to the issue. Summary of Background Data: Wrong site surgery is one of the most common events reported to The Joint Commission. It has been reported that 50% of spine surgeons experience at least 1 wrong site surgery in their career, with events leading to signficant harm to patients. Materials and Methods: We examined incorrect level spine surgery adverse events reported to the VHA National Center for Patient Safety (NCPS) from 2000 to 2017. A rate of wrong site spine surgery was determined by dividing the number of wrong site cases by the total number of spine surgeries during the study period. Similarly, a rate of wrong site surgery by orthopedist and neurosurgeons was calculated. Results: There were 32 reported cases of wrong site spine surgery between 2000 and 2017. Fourteen cases involved the cervical region, 13 the lumbar region, and 5 the thoracic region. The majority of the root causes (69% or 48 of 69 root causes) fell into 2 broad categories: problems with the radiograph or problems with the intraoperative marker. These were not mutually exclusive and several root cause analyses involved >1 of these issues. Conclusions: Wrong level surgery of the spine is a significant safety issue facing the field that continues to occur despite surgical teams following guidelines. As poor radiograph quality and interpretability were the most common root causes of these events, interventions aimed at optimizing image quality and accurate interpretation would be a logical first action. Abstract : Supplemental Digital Content is available in the text.